Mean Energy Flux, Associated Derived Height‐Integrated Conductances, and Field‐Aligned Current Magnitudes Evolve Differently During a Substorm. Issue 2 (9th February 2023) - Carter, J. A.; Milan, S. E.; Forsyth, C.; Lester, M. E.; Walach, M.‐T.; Gjerloev, J.; Paxton, L. J.; Anderson, B. J.
Abstract: We examine the average evolution of precipitation‐induced height‐integrated conductances, along with field‐aligned currents (FACs), in the nightside sector of the polar cap over the course of a substorm. Conductances are estimated from the average energy flux and mean energies derived from auroral emission data. Data are binned using a superposed epoch analysis on a normalized time grid based on the time between onset and recovery phase ( δ t ) of each contributing substorm. We also examine conductances using a fixed time binning of width 0.25 hr. We split the data set by magnetic latitude of onset. We find that the highest conductances are observed for substorms with onsets that occur between 63 and 65° magnetic latitude, peaking at around 11 mho (Hall) and 4.8 mho (Pedersen). Substorms with onsets at higher magnetic latitudes show lower conductances and less variability. Changes in conductance over the course of a substorm appear primarily driven by changes (about 40% at onset) in the average energy flux, rather than the average energy of the precipitation. Average energies increase after onset slower than energy flux, later these energies decrease slowly for the lowest latitude onsets. No clear expansion of the main region 1 and region 2 FACs is observed. However, we do see an ordering of the current magnitudes with magnetic latitude of onset, particularly for region 1 downwards FAC in the morning sector. Peak current magnitudes occur slightly after or before the start of the recovery phase for the normalized and fixed‐time grids. Plain Language Summary: Particles precipitate from Earth's magnetosphere into the upper ionosphere causing auroral emissions. A comparison of these auroral emissions, taken at different wavelengths, can be used to estimate the mean energy of the particles, as well as the flux, or number of precipitating particles in an area per unit time. From this mean energy and flux, we can estimate changes in the conductance of the ionosphere. Here, we examine how the conductance varies during the course of a substorm; when increased auroral emissions are seen suddenly on the nightside of the Earth. For this work we use imaging data from low‐altitude spacecraft that give reasonable spatial coverage of the nightside ionosphere. We compare the changes in conductance over the course of an average substorm, to those seen in electrical currents that flow in the Earth's magnetosphere. The currents respond in a similar manner to the parameters derived from the auroral emissions. Key Points: We track the progression of mean energy and mean energy flux, derived conductances, and field‐aligned currents (FACs), during substorms Low‐latitude onsets exhibit the largest and longest‐lived changes to height‐integrated conductance Latitude of substorm onset has less control on FAC magnitudes